Exploring Turnover Intentions: The Impact of Job Satisfaction and Organizational Constraints on Indian Employees in Multinational Corporations - Harsimran Kaur; Sarabjit Kaur Sran, (Research and Review: Human Resource and Labour Management (p-ISSN: 3049-4125), 2024)
This research explores the connections and gender-related variations within employee satisfaction, workplace constraints, and intentions to leave among Indian employees at Multinational Corporations (MNCs). The study used purposive sampling to select 114 participants across various departments and sectors, comprising 58 males and 56 females. It focused on employees aged 18-64, employing scales developed by Paul Spector: the Satisfaction Survey, Organizational Constraints Scale, and Turnover Intentions Survey. Pearson's correlation metric was used to analyze the relationships among these variables. The results revealed negative correlations between work satisfaction, organizational constraints, and turnover intentions. Additionally, t-tests showed no significant gender differences in job satisfaction and organizational constraints, although males demonstrated higher turnover intentions.